Disaster Planning for Caregivers - Carolyn Wilken (EDIS, 2012)
“News that a hurricane or tornado is on its way can cause anyone to worry. But if you’re responsible for providing care for someone who’s disabled, chances are you face additional concerns. You and the person you care for may not be able to “jump and run” when the tornado sirens are sounded or the hurricane warning is issued. As a caregiver, you should have specific strategies to be prepared for any natural disaster that may come your way.” This 2-page Family Album Radio transcript was written by Carolyn Wilken and published by the UF Department of Family, Youth and Community Sciences, March 2012.